2016
DOI: 10.4173/mic.2016.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Glucose Sensing is Sometimes Surprisingly Rapid

Abstract: Rapid, accurate and robust glucose measurements are needed to make a safe artificial pancreas for the treatment of diabetes mellitus type 1 and 2. The present gold standard of continuous glucose sensing, subcutaneous (SC) glucose sensing, has been claimed to have slow response and poor robustness towards local tissue changes such as mechanical pressure, temperature changes, etc. The present study aimed at quantifying glucose dynamics from central circulation to intraperitoneal (IP) sensor sites, as an alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 16 publications
0
20
1
Order By: Relevance
“…Glucose sensing in the peritoneal space has been studied in rabbits [ 30 ], rats [ 31 , 32 ] and pigs [ 22 , 33 ]. Burnett et al reported the mean time delay and mean time constant to be 40.8 (SD 34.8) seconds and 5.6 (SD 2.9) minutes, respectively [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucose sensing in the peritoneal space has been studied in rabbits [ 30 ], rats [ 31 , 32 ] and pigs [ 22 , 33 ]. Burnett et al reported the mean time delay and mean time constant to be 40.8 (SD 34.8) seconds and 5.6 (SD 2.9) minutes, respectively [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Burnett et al reported the mean time delay and mean time constant to be 40.8 (SD 34.8) seconds and 5.6 (SD 2.9) minutes, respectively [ 22 ]. Fougner et al have previously found a mean time delay of 9.7 (SD 9.5) seconds and mean time constant of 4.7 (SD 2.9) minutes in pigs [ 33 ]. The IP glucose dynamics (time delays and time constants) in the present investigation are slower compared to these previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IP route is currently being investigated (Burnett et al, 2014;Fougner et al, 2016). A quick onset of the glucoselowering effect of administered insulin significantly contributes to the performance of meal compensation.…”
Section: Discussionmentioning
confidence: 99%
“…Reported mean values for SC glucose appearance including the sensor dynamics in pigs are τ G = 13 min and θ G = 2 min (Burnett et al, 2014), while faster dynamics of τ G = 6 min and θ G = 1 min have been observed for peritoneal glucose sensing in pigs (Burnett et al, 2014;Fougner et al, 2016). However, the SC route excluding sensor dynamics can be as fast as τ G = 5 min and θ G = 1 min for single subjects under well controlled clinical conditions (Basu et al, 2015).…”
Section: Sub-model Of Glucose Sensingmentioning
confidence: 99%